Comparative transcriptional profiling of the early host response to infection by typhoidal and non-typhoidal Salmonella serovars in human intestinal organoids. - Basel H Abuaita (Public Library of Science (PLoS), 2021)
Salmonella enterica represents over 2500 serovars associated with a wide-ranging spectrum of disease; from self-limiting gastroenteritis to invasive infections caused by non-typhoidal serovars (NTS) and typhoidal serovars, respectively. Host factors strongly influence infection outcome as malnourished or immunocompromised individuals can develop invasive infections from NTS, however, comparative analyses of serovar-specific host responses have been constrained by reliance on limited model systems. Here we used human intestinal organoids (HIOs), a three-dimensional "gut-like" in vitro system derived from human embryonic stem cells, to elucidate similarities and differences in host responses to NTS and typhoidal serovars. HIOs discriminated between the two most prevalent NTS, Salmonella enterica serovar Typhimurium (STM) and Salmonella enterica serovar Enteritidis (SE), and typhoidal serovar Salmonella enterica serovar Typhi (ST) in epithelial cell invasion, replication and transcriptional responses. Pro-inflammatory signaling and cytokine output was reduced in ST-infected HIOs compared to NTS infections, consistent with early stages of NTS and typhoidal diseases. While we predicted that ST would induce a distinct transcriptional profile from the NTS strains, more nuanced expression profiles emerged. Notably, pathways involved in cell cycle, metabolism and mitochondrial functions were downregulated in STM-infected HIOs and upregulated in SE-infected HIOs. These results correlated with suppression of cellular proliferation and induction of host cell death in STM-infected HIOs and in contrast, elevated levels of reactive oxygen species production in SE-infected HIOs. Collectively, these results suggest that the HIO model is well suited to reveal host transcriptional programming specific to infection by individual Salmonella serovars, and that individual NTS may provoke unique host epithelial responses during intestinal stages of infection.